Surveillance of aedes vectors in selected agricultural, fogging-free and dengue-prone areas in Peninsular Malaysia - Wan-Norafikah, Othman; Chen, Chee Dhang; Mohd-Amir, Mohd Hanafie; Azahari, Abdul Hadi; Zainal-Abidin, Abu Hasan; Nazni, Wasi Ahmad; Mariam, Mohamad; Mohd-Shahizan, Jamil; Sofian-Azirun, Mohd (SEAMEO Regional Tropical Medicine and Public Health Network, 2019)
Distributions of Aedes vectors in fifteen study sites comprising of ag-ricultural, fogging-free and dengue-prone areas in Peninsular Malaysia were investigated using ovitraps during January and May 2016 placed indiscriminately inside and outside human premises in all study sites. Cheras, Federal Territory of Kuala Lumpur, a dengue-prone area showed the highest ovitrap index (OI) (96.00%) while the lowest OI (64.00%) was found in both Padang Serai, Kedah and Temerloh, Pahang, fogging-free residential areas. Aedes albopictus was the most dominant species in all study sites while Ae. aegypti was captured in only five study sites. Mean number of larvae per recovered ovitrap among various species is significantly different for all types of areas except for oil palm planta-tions. The existence of Ae. aegypti in a few and Ae. albopictus in all study sites suggest their roles in the current and forthcoming transmission of dengue virus in these study sites. © 2019, SEAMEO TROPMED Network. All rights reserved.